2011
DOI: 10.1556/aphysiol.98.2011.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Specific alterations of physiological parameters in competitive race walkers

Abstract: Race walking is the technical and athletic expression of fast walking and it can be considered as a type of endurance performance. The purpose of this study was to examine whether 12 weeks of a specially designed training program results in the further training enhancement of endurance performance and the related physiological parameters in already well-trained race walkers competing at the national and international level. The investigation protocol consisted of determining the maximal oxygen uptake (VO2peak)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The practical example of applying the theoretical basis was made during the Women's Greek Championship (Megara 2016), in which 12 athletes of race walking aged 19 to 40 participated (28.50 ± 7.20). Athletes had experience in endurance training in race walking for at least 5 years [15,16]. A prerequisite for their participation in the study was their ability to have reached the qualifying thresholds for the Race-Walking National Championships, which means that these athletes had a high level of training experience and endurance [17].…”
Section: Methodsmentioning
confidence: 99%
“…The practical example of applying the theoretical basis was made during the Women's Greek Championship (Megara 2016), in which 12 athletes of race walking aged 19 to 40 participated (28.50 ± 7.20). Athletes had experience in endurance training in race walking for at least 5 years [15,16]. A prerequisite for their participation in the study was their ability to have reached the qualifying thresholds for the Race-Walking National Championships, which means that these athletes had a high level of training experience and endurance [17].…”
Section: Methodsmentioning
confidence: 99%
“…16 Notably, the longer the duration of the menstrual dysfunction the larger the bone mineral deficit at non-weight-bearing sites.14 A recent study demonstrated that bone metabolism markers in females with menstrual cycle dysfunction correlated; though bone reformation occurred at a faster rate in athletes compared with controls and a biomarker indicated that bone disintegrated at a higher rate in the amenorrhea and oligomenorrhea group than in the group of postmenopausal females with osteoporosis.17 Furthermore, these values were significantly above the recommended upper values. 17 Most recent research has proposed what the long term consequences of the female athlete triad are. Delays in menarche or periods of amenorrhea during adolescence may increase risk for osteoporosis later in life because peak bone accrual occurs during adoles cence.14 The concept that the "bone bank" is already depleted once bone reabsorption begins to occur in the 20s was introduced.14 Peak bone mass in the femur was found to occur during adolescence, while peak bone mass in the lumbar spine occurred later in life.…”
Section: Education and Awareness Of The Accultur Ation Of Commonalitymentioning
confidence: 99%
“…On the other hand, long test protocols may also result in slightly lower registered VO 2max values due to increased body temperature, significant dehydration, muscle pain, and loss of motivation of the examinee (20,21). In certain cases, it is necessary to choose a specific test protocol that is most appropriate to the characteristics of the sport in question (3). The use of sport-specific ergometers in laboratory testing enables more precise endurance measurements due to a more true to life reproduction of a dynamic stereotype that is characteristic of the sport and enables better mechanical efficacy (with lower energy consumption) during the test execution.…”
Section: Cardiorespiratory Endurancementioning
confidence: 99%
“…The combination of spiroergometric testing (with appropriate testing protocols) and the measurements of the lactate thresholds is believed to be the gold standard in the assessment of cardiorespiratory endurance. The generated parameters are then used to define the training objectives, to prepare a precise training plan and program, and to evaluate the effects of the subsequent training effect evaluation for (3,24). The most obvious shortcoming of such an approach is its high economic price, limiting its use to only the top athletes and preventing its use by young talented athletes for whom training program corrections would represent the method to achieve top results.…”
Section: Cardiorespiratory Endurancementioning
confidence: 99%